PENGARUH PENAMBAHAN SARI BUAH JAMBU BIJI MERAH (Psidium guajava L.) DAN GLUKOSA TERHADAP TOTAL BAKTERI ASAM LAKTAT DAN KARAKTERISTIK ORGANOLEPTIK MINUMAN SINBIOTIK CINCAU HIJAU (Premna oblongifolia Merr) - Rizal, Samsul; Nurainy, Fibra; Fitriani, Melza (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2013)
The purpose of this research was to determine the concentration of guava concentrate (Psidium guajava L.) and glucose which produce green cincau sinbiotic beverage with the best sensory characteristics. Factorial treatment was arranged in a Complete Randomized Design (RAKL) with two factors and three replications. The first factor was the concentration of guava concentrate (K), consisted of 5 levels (0%, 5%, 10%, 15%, and 20%), and the second factor was the addition of glucose (G) that consisted of 3 levels (2%, 3%, and 4%). Data homogeneity and additivity were analyzed by Barlett and Tuckey tests. Data were analyzed with Analysis of Varians, then the data were further analyzed with orthogonal polynomial at significant level of 5% or 1%. The results showed that the addition of 15% guava concentrate and 2% of glucose produced the best characteristic of green cincau sinbiotic beverage with concentration of lactic acid bacteria 11.209 log colonies / ml, taste of 3.48 (rather like), flavor 3.35 (rather like), the appearance of 3.18 (rather like) and 3.57 overall acceptance (like), and antioxidant activity of 67.14%. Keywords: Glucose, green cincau sinbiotic baverage, guava concentrate